MODEL PENGELOLAAN PERIKANAN BERBASIS HUKUM ADAT LAOT DI LHOK RIGAIH KABUPATEN ACEH JAYA - Sulaiman Sulaiman (Masalah-Masalah Hukum, 2011)
The concept of fisheries management in Indonesia, local wisdom to know the content community, as the Regulation No. 4512009 and Regulation no. 1112006. This study wanted to address how the model-based fisheries management /aot customary law in Aceh. This research uses socio-legal research methods. In addition to legal material, also conducted observations and interviews with informants. The study found that sea of customary law in Aceh is customary provisions that are relevant to fisheries management model oriented to environmental sustainability and welfare. The value of local wisdom that lives within the community can become an alternative model in fisheries management in Indonesia towards environmental sustainability and welfare-oriented fishermen.